THE USE OF DIGITAL LIBRARY BY ART UNDERGRADUATES IN SRI LANKA: A CASE STUDY AT UNIVERSITY OF PERADENIYA - Hindagolla, B (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of this paper is to explore the understanding of digital library use and its acceptance by arts undergraduates in Sri Lanka. Survey research design was applied and 150 undergraduates were selected as sample of the study. Structured questionnaire was used to gather data and total of a 132 respondents completed the survey, resulting in a response rate of 88 %. All the respondents use the library and majority of them are aware of the digital library. The most popular methods of students’ becoming aware of the digital library are, through library website and library staff. Study found that more than half of respondents’ use digital library and there is a notable gap between awareness and the usage of the digital library. Present study identified some factors for not using the digital library. Overall, majority of digital library users are satisfied with the services, and system characteristics of the digital library, but average percentage of users are satisfied with the current methods applied by the library to make the users aware about the digital library information. It is notable mark to library management to improve more services for user benefits. The most significant finding was that students who use the digital library they perceived that it is important to their studies and students have realized the usefulness of the digital library. As users are having positive attitudes about this system, they intend to use it more for their learning and research in future. But users recommend that people would be more likely to use the digital library, if they are provided with proper training and awareness programs on digital information use.